(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2024)
The aim of the article is to show the difference between the philosophical and religious concepts of God as transcendence. Both philosophy and religion refer to the idea of transcendence; however, according to the author of this paper, the concept is used in slightly different ways. In philosophy, the concept of transcendence has a radical meaning, i.e. God is understood as being absolutely distinct from our world and completely unknowable. In religion, on the other hand, the notion of transcendence has a less radical meaning because only in this way can the main aim of religion, which is to develop a relationship with God, be achieved. This article provides examples of how the transcendence of God was interpreted religiously, in particular, how this concept was understood by negative theology, Protestant theology and Catholic theology. In addition, the author argues against the philosophical criticism of religion, which is based on the assumption that since God is transcendent, all religions do not concern the true God, but rather a false idol, and therefore they are considered idolatry.